The Role of Strategic Planning on the Management of Organizational Change - Fragouli, Evangelia; Yankson, Joana Kwaw (Financial Risk and Management Reviews, 2015)
Strategic planning is very crucial in a successful change management. This is because a successful change management is a catalyst to the survival of any organisation in the face of continuously competitive business environment. However, the introduction of these changes, tends to be problematic and part of a puzzle. The present study seeks to illustrate the importance of strategic planning as a fundamental tool in a successful management of change in overcoming the complexities that accompany change. It is a literature review based study which concludes that the focus on change implementation in change processes alone is not enough to provide robust results of change goals. Consequently, organisations which adopt strategic planning as a fundamental tool at the early stages of their change processes tend to gain an advantage of achieving change goals.